2002
DOI: 10.1542/peds.109.6.e89
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Analysis of Platelet Transfusion Usage Among Neonates on Extracorporeal Membrane Oxygenation

Abstract: ABSTRACT. Objective. Multiple platelet transfusions are invariably given to neonates on extracorporeal membrane oxygenation (ECMO), and no alternative to repeated transfusions exists. Before any alternatives, such as administration of thrombopoietic stimulators, could be contemplated, data regarding the number of platelet transfusions received by neonatal ECMO patients is needed, and the mechanisms that cause the thrombocytopenia of these patients must be better defined. As a step toward determining this, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Previous literature proposed that platelet levels were important in predicting intracranial hemorrhage when platelet counts were <200,000/mm 3 (31), when platelet counts were difficult to maintain (32), or with increasing platelet transfusion requirements (33). Further research found a significant correlation between the total number of platelet transfusions and the length of the ECMO run (34), attributing the large need for platelet transfusions during ECMO because of impairment of platelet function (35-37). Although the mechanisms of platelet dysfunction are not completely understood, several researchers believe it is the result of deficiency of platelet agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature proposed that platelet levels were important in predicting intracranial hemorrhage when platelet counts were <200,000/mm 3 (31), when platelet counts were difficult to maintain (32), or with increasing platelet transfusion requirements (33). Further research found a significant correlation between the total number of platelet transfusions and the length of the ECMO run (34), attributing the large need for platelet transfusions during ECMO because of impairment of platelet function (35-37). Although the mechanisms of platelet dysfunction are not completely understood, several researchers believe it is the result of deficiency of platelet agonists.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,19 Future randomized trials, using different transfusion 'trigger levels' would be helpful in assessing this issue. Similarly, we are aware of little evidence to support giving erythrocyte transfusions to non-bleeding, non-mechanically ventilated NICU patients with a hemoglobin >9 g per 100 ml.…”
Section: Discussionmentioning
confidence: 99%
“…These include persistent pulmonary hypertension, congenital diaphragmatic hernia, meconium aspiration syndrome, respiratory distress syndrome, pneumonia, severe air-leak syndromes, sepsis and septic shock. (1,2) Even though lifesaving, ECMO introduces a high risk of complications including intravascular haemolysis, bleeding or clot formation, inflammation and sepsis. (3,4) Thrombocytopenia in neonates is a major problem in neonatal intensive care units (NICU), as studies have shown the association of thrombocytopenia with increased mortality, length of hospital stay as well as some major comorbidities such as intraventricular haemorrhage, disseminated intravascular coagulopathy and necrotising enterocolitis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impedance method allows for the differentiation of different cell lineages, such as platelets and red blood cells (RBCs), based on the cell size. (1,5) This is sufficient when platelet and RBC size are normal. However, in cases of abnormal platelet (large platelets) or RBC (microcytes, shizocytes) size, cell fragments, and less commonly, bacteraemia and cryoglobulins, impedance platelet counting is subjected to interferences because of overlap between RBCs and platelets and is therefore inadequate as a method for counting platelets.…”
Section: Introductionmentioning
confidence: 99%